Analysis of package programs used in the study of fiber optic communication systems (MMIT Proceedings, 2025)
An analysis of the package programs used in the study of fiber-optic communication systems is considered. The reason is that currently various levels of difficulty arise in providing higher educational institutions with laboratory equipment in the educational process. One of the most significant challenges in equipping laboratories is the high cost of laboratory equipment (the cost of one stand can amount to several hundred million soums)